0259 Shiftworkers are at Increased Risk of Developing Chronic Pain and Opioid Use Disorders: A Study of 116, 000 UK Biobank Participants Over a Decade. (27th May 2020) - Gao, L; Li, P; Cui, L; Luo, Y; Vetter, C; Saxena, R; Scheer, F A; Johnson-Akeju, O; Hu, K
Abstract: Introduction: In the current epidemic of opioid-related deaths, and widespread use of opioids to treat chronic pain, there is a pressing need to understand the underlying risk factors that contribute to such devastating conditions. Shiftwork has been associated with adverse health outcomes. We tested whether shiftwork during middle age is linked to the development of chronic pain and opioid misuse. Methods: We studied 116, 474 participants in active employment between 2006–2010 (mean age 57±8; range 37–71) from the UK Biobank, who have been followed for up to 10 years until 2017. We included participants who were free from all forms of self-reported pain, and were not taking opioid medications at baseline. Chronic pain and opioid use disorder diagnoses were determined using hospitalization records and diagnostic coding from ICD-10. Multivariate logistic regression models were performed to examine the associations of shiftwork status (yes/no) and nightshift frequency (none/occasional/permanent) and with incident chronic pain and/or opioid use disorder during follow-up. Models were adjusted for demographics, education, Townsend deprivation index, major confounders (BMI, diabetes, bone fractures/injuries, operations, peripheral vascular disease, joint/inflammatory diseases, cancer, standing/manual labor at work) and covariates (smoking, alcohol, high cholesterol, depression/anxiety, and cardiovascular diseases). Results: In total, 190 (1.6/1, 000) developed chronic pain or opioid use disorders. Shiftworkers (n=17, 673) saw a 1.5-fold increased risk (OR 1.56, 95% CI: 1.08–2.24, p =0.01) relative to day workers. Within shiftworkers, those who reported occasional nightshift work (n=3, 966) were most vulnerable (OR 1.57, 95% CI: 1.06–2.34, p =0.02). Results remained similar after adjusting for baseline sleep duration, chronotype and insomnia. Conclusion: Shiftwork, and in particular rotating nightshift work is associated with increased risk for developing chronic pain and opioid use disorders. Replication is required to confirm the findings and to examine underlying mechanisms. Support: This work was supported by NIH grants T32GM007592, RF1AG064312, and RF1AG059867.